Validity and Reliability of Persian Version of COMI-Neck Questionnaire in Iranian Patients with Chronic Neck Pain - Morteza Rafatifard; Shabnam Shahali; Soheil Mansour Sohani (Function and Disability Journal, 2018)
Background and Objectives: Chronic neck pain in various ages is one of the important causes of occupational disability which has imposed huge costs on health services. Therefore, developing a valid and reliable instrument to obtain information about patients with neck pain seems necessary. The present study was conducted to examine the psychometric properties of COMI-Neck questionnaire in Iranian patients with chronic neck pain. Methods: In this study, in order to examine reliability (test-retest and internal consistency), the Persian version of The Core Outcome Measures Index for the neck (COMI-Neck), was completed using convenience sampling method among 100 patients with chronic neck pain attending rehabilitation clinics in Karaj city. In order to examine validity, FRI, NDI and SF-36 questionnaires were also completed by participants. Internal consistency, reliability, discriminate validity and construct validity were analyzed using SPSS 20 and statistical tests. Results: The ICC test results for scores of 5 indices including pain, daily activities, adaptability to existing symptoms, quality of life, recreational and social activities in COMI-Neck, showed that very high validity of the questionnaire with Cronbach’s alpha of 0.89. There was strong correlation between the total score of COMI-Neck and the total score of FRI (P<0.05). Also, a strong correlation existed between the total score of COMI-Neck and NDI total score (P<0.05). Strong and reverse correlations were observed between score of all scales of COMI-Neck and the total score of SF-36 (P<0.05). Conclusion: The Persian version of The Core Outcome Measures Index for the neck (COMI-Neck) showed good validity and reliability in evaluation of outcome measures among Iranian patients with chronic neck pain.